Exploring the experience of adhering to a prescribed pre-surgical exercise program for patients with advanced rectal cancer: A phenomenological study. (March 2015) - Burke, Shaunna M.; West, Malcolm A.; Grocott, Michael P.W.; Brunet, Jennifer; Jack, Sandy
Abstract: Objectives: The aim of this study was to explore the lived experience of patients with advanced rectal cancer as they attempted to adhere to a prescribed, hospital-based pre-surgical exercise program. Design/Methods: Ten patients took part in three semi-structured in-depth interviews prior to (week 0), midway (week 3), and at completion (week 6) of the exercise program. Data were analysed using a phenomenological approach. Results: Main themes that were deemed important for remaining enrolled in the program included: (1) building camaraderie and peer support, (2) experiencing a sense of structure and control, and (3) feeling safe and encouraged. Patients also reported engaging in further exercise outside the program and feeling motivated to continue exercising in the future. Conclusions: This study shows the potential to integrate exercise prior to surgery as it was viewed as acceptable and feasible by patients with advanced rectal cancer. Moreover, it provides much needed information into the possible mechanisms that underpin patient's continued participation in exercise programs during treatment for advanced rectal cancer. Prescribed, hospital-based program should be implemented to promote opportunities for exercise and provide on-going supportive care options for patients awaiting surgery. Highlights: Exercise prior to surgery is viewed as feasible by some patients with advanced rectal cancer. The meaning of adhering to a pre-surgical exercise program is holistic and multidimensional. Mechanisms that underpin continued participation in pre-surgical exercise are contextual and may change over time.